COALBED METHANE (CBM) FIELD DEVELOPMENT STUDY IN INDONESIA USING RESERVOIR SIMULATION : BLOCK S CASE IN SOUTH SUMATERA - NOVIASTA (NIM : 22210021), BONAR
Coalbed methane (CBM) is one of the unconventional gas resources developed by the Government of Indonesia. Gas production from CBM reservoir is started with dewatering process or producing water from the reservoir. The produced CBM gas is potentially commercialized since dewatering period by combining it with conventional natural gas through main gas pipeline. Utilizing reservoir simulation, this research studies a field development of an actual CBM field in Indonesia, and uses the results to evaluate the economic fasibility of selling CBM gas through the main gas pipeline. An economic sensitivity analysis is also conducted to learn about the effect of operation & economic parameter changes. A CBM data set of Block S is gathered from the operator company to be the input of reservoir simulation. With a maximum limit of 1000 wells, three (3) field development scenarios, which are non-aggressive (1), moderate (2), and aggressive (3), are simulated to get estimations of production profile. Using those production profile estimations, economic evaluation and sensitivity analysis are done based on main gas pipeline tie-in scheme. Gas recovery potential achieved by 1000 wells field developments of scenario 1, 2, and 3, are 30.51%, 36.27%, dan 41.34% consecutively. At US$ 5 / MCF base gas price, moderate development (2) and aggressive development (3) scenario are economically feasible, while non-aggressive development (1) scenario is not economically feasible. The minimum gas price of US$ 5.92 / MCF is required to achieve an economic feasibility of non-aggressive development (1) scenario. Hydraulic fracturing can potentially increase gas recovery by maximum of 3.5%, 3.52%, dan 3.59% respectively for scenario 1, 2, and 3. Increasing pump RPM to shorten dewatering period may potentially increase gas recovery by maximum of 3.7%, 4.76%, dan 5.08% consecutively for scenario 1, 2, and 3. The aggressive development scenario (3) is the most economically sensitive among all scenarios. All those three (3) scenarios are most sensitive to gas price changes, and least sensitive to operating cost (OPEX) changes.